Очистка теплосетевой воды электромембранным методом - Антонов, Алексей Валентинович (НТУ "ХПИ", 2016)
Разработана технология комбинированного инертного анода не содержащего в своем составе благородных металлов и надежно работающего в процессе электролиза хлоридно-сульфатных растворов. На этой основе разработана стендовая установка электромембранного умягчения воды и проведены её стендовые испытания. Резко снизилось потребление реагентов, а энергозатраты составили всего 1,3 кВт∙ч/м³ обработанной воды. Полученная вода имеет карбонатный индекс 0,09 (мг-экв/дм³)² и может быть использована для подпитки теплосети.

A method was developed to make a combined inert anode of plumbum dioxide on the titanium dioxide-manganese substrate that contains no precious metals and operates reliably during the electrolysis of chloride-sulfate solutions. On this basis the test unit for the electro-membrane water softening was developed and it was subjected to the bench tests. The technology consists in that the water passes through the cathode chambers of two-chamber membrane electrolyzer, including the separation of settled hardness salts, additional water softening in the sodium cation-exchange unit and its neutralization when it passes through the anode chambers of the electrolyzer. A number of required reagents is sharply decreased, and the amount of discharged mineralized drainages is also decreased, and the energy expenditures made up only 1,3 kW∙h/m³ of wastewater. The produced water has a carbonate index of 0,09 (mg-ekV/dm³)² and after the pH adjustment by ammonia it can be used to feed the heating system.
Treatment of the heating system water using the electro-membrane method
Keywords: металл-оксидный анод; электромембранное умягчение; карбонатный индекс; водоподготовка; питательная вода; соли жесткости; metal-oxide anode; electromembrane softening; carbonate index